(untitled) (Caligrama: Revista de Estudos Românicos, 2019)
Resumo: The objective of this article is to outline a discursive ethos profile from the meaning effects instituted by linguistic elements in two songs by the Brazilian singer, violinist and songwriter Nando Reis. For this purpose, two of the singer’s musical career albums were selected, being one from his career in the group Titãs and the other from his solo career. Subsequently, one song was randomly selected from each album and the linguistic mechanisms that possibly enhanced the speaker’s self-image construction were identified and analyzed. Finally, the discursive ethos profile that emerges from linguistic materialities was interpreted. In order to achieve such objective, the theoretical assumptions from the Linguistics of Enunciation were used as basis, mainly from Émile Benveniste’s theory and his definitions of “language”, “enunciation” and “subjectivity”. Moreover, other theoretical branches were adopted for the concept of ethos, from the Discourse Analysis perspective, by Dominique Maingueneau (2005) and debreagem, from Semiotics, by Greimas e Courtés (2008). To support the methodological parameter, Carlo Guinzburg’s (1989) indiciary paradigm was used. Lastly, enunciative matters were reflected upon, from the analysis of meaning production instituted by linguistic elements in the analyzed songs. Palavras-chave: ethos discursivo; enunciação; produção de sentidos. Abstract: The objective of this article is to outline a discursive ethos profile from the meaning effects instituted by linguistic elements in two songs by the Brazilian singer, violinist and songwriter Nando Reis. For this purpose, two of the singer’s musical career albums were selected, being one from his career in the group Titãs and the other from his solo career. Subsequently, one song was randomly selected from each album and the linguistic mechanisms that, possibly, collaborated for the speaker’s self-image construction were identified and analyzed. Finally, the discursive ethos profile that emerges from the linguistic materialities was interpreted. In order to achieve such objective, the theoretical assumptions from the Linguistics of Enunciation were used as basis, mainly from Émile Benveniste’s theory and his definitions for “language”, “enunciation” and “subjectivity”. Moreover, other theoretical branches were adopted for the concept of ethos, from the Discourse Analysis perspective, by Dominique Maingueneau (2005) and debreagem, from Semiotics, by Greimas e Courtés (2008). To support the methodological parameter, Carlo Guinzburg’s (1989) indiciary paradigm was used. Lastly, enunciative matters were reflected upon, from the analysis of meaning production instituted by linguistic elements in the analyzed songs. Keywords: discursive ethos; enunciation; meaning production.